Analisis Abreviasi Teks Berita Lokal Pertamax Oplos Edisi Februari-April 2025 - Sila Rahmatina; Anindya Oktaviona Ervinawati; Adilah Puja Rahmawati; Mohamad Afrizal (Semantik : Jurnal Riset Ilmu Pendidikan, Bahasa dan Budaya, 2025)
This study aims to analyze the forms and functions of abbreviations in local news texts covering the “Pertamax Oplos” issue during the period of February to April 2025. The main focus is on two types of abbreviations initialisms and acronyms which are frequently used in local online media such as Jawa Pos Radar Solo, Detiknews, and AntaraNews. This research employs a descriptive qualitative method, using observation and note-taking techniques to identify abbreviation forms in written texts. The findings reveal 20 abbreviation data points, consisting of 13 initialisms and 7 acronyms, consistently used in headlines, leads, and the body of the news. The use of abbreviations not only reflects linguistic efficiency in journalistic writing but also demonstrates how local media adapt to the demands of fast, concise, and easily comprehensible communication. These findings emphasize the significant role of abbreviations in shaping the language style of local media and highlight their importance in modern linguistic practices within digital contexts. This study is expected to contribute to applied linguistic research and support effective media writing practices.